Analysis of Carbon Sequestration Rate in Seaweed (Kappaphycus alvarezii) Based on Environmental Mitigation - Muhammad Sahir; Isma Riskiani; Uttari Dewi; Muhammad Yusfi Yusuf (Universitas Gadjah Mada, 2023)
Blue economy is a development concept that develops by relying on marine or aquatic resources. An increase in carbon dioxide (CO2) in the atmosphere is fueling climate change. This study aims to analyze the rate of carbon uptake in the waters, using seaweed Kappaphycus alvarezii which utilizes carbon to be converted into biomass before returning to the air. The results showed that highest carbon absorption rate was found in location A with the highest total carbon absorption of 94.87±0.77 tons C/planting cycle, then treatment B with 83.96±0.54 tons C/planting cycle, and the lowest in treatment C with 76.88±0.18 tons C/planting cycle. Water quality parameters are still mostly in decent condition for the cultivation of Kappaphycus alvarezii seaweed. Salinity conditions of waters are relatively high (35-39 ppt) even though the optimum seaweed grows in the range of 30-34 ppt. The conclusion of the study is that the highest total carbon is found at Location A, which is 94.87±0.77 tons C/planting cycle. The suggestion of this study is that it is necessary to analyze the suitability of seaweed cultivation land with various water quality parameters, so that mapping of potential types of seaweed that can be cultivated according to the characteristics and quality of the waters.